Management of polyethylene glycol solution aspiration using bronchoscopic lavage in a dog - Aguayo Santaella, Daniela M. (J Vet Intern Med, 2020)
Polyethylene glycol lavage solutions are used for colonic preparation in dogs and are considered relatively safe. Aspiration is an uncommon but potentially devastating complication of polyethylene glycol administration. Full recovery is possible and often rapid in people treated with bronchoalveolar lavage. A healthy 2‐year‐old male Beagle used in an endoscopy teaching laboratory aspirated a small amount of polyethylene glycol lavage solution. Although initially appearing unaffected, the dog quickly became hypoxemic. Bronchoscopy was used to lavage the lungs and aspirate tracheal/pulmonary fluid 5 times over the course of 45 minutes. The dog completely recovered. This report presents the successful treatment of polyethylene glycol aspiration in a dog. Although the seriousness of aspiration might not be immediately evident, bronchoscopy and lavage should be pursued because of the rapidly progressive nature of polyethylene glycol‐induced pulmonary edema.